Assessing symmetry of zygomatic bone through three-dimensional segmentation on computed tomography scan and "mirroring" procedure: A contribution for reconstructive maxillofacial surgery. Issue 4 (April 2018) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Oliva, Antonio Giancarlo; Termine, Giovanni; Pucciarelli, Valentina; Dolci, Claudia; Sforza, Chiarella
Abstract: Purpose: Surgical reconstruction of zygomatic bones in cases of traumatic injuries is a frequent event: assessment of symmetry is mandatory for a correct restoration of zygomatic shape, but the literature is discordant about its quantification. The purpose of this study is to show a novel method for assessing symmetry of zygomatic bone through mirroring of 3D models segmented on CT-scan. Materials and methods: A total of 100 patients (50 male and 50 female), divided into two age groups (18–49 years and 50–92 years) were selected from the computed tomography (CT) scan database of a hospital in northern Italy. Zygomatic bones from each patient were segmented, and the left bone was automatically mirrored and registered on the right one according to the least point-to-point distance between the two surfaces. The mean and root mean square (RMS) distance between the two models was then calculated. Statistically significant differences according to sex and age groups were assessed through two-way analysis of variance (p < 0.05). In addition, the effect size of differences was calculated. Results: The method proved to be repeatable, with inter- and intraoperator errors lower than 5%. Overall, mean and RMS point-to-point distances were respectively 0.01 mm and 0.84 mm, without statistically significant differences according to sex or age (p > 0.05), and with negligible effect size. Conclusion: This study provides an innovative method for assessing the symmetry of the zygomatic bone based on surface analysis. Results may provide useful indications for the reconstruction of zygomatic bones in maxillofacial surgery.